PROBLEMATIKA PEMBELAJARAN MATEMATIKA MENGGUNAKAN E-LEARNING MADRASAH KELAS XI - Anggun Fitriani; Mohamad Rif'at; Dede Suratman (Jurnal AlphaEuclidEdu, 2022)
This research aims to describe the implementation of mathematics learning using madrasah e- learning by mathematics teachers at Madrasah Aliyah Negeri (MAN) 2 Pontianak and describe the problems faced by them, and the issues faced by students of class XI Madrasah Aliyah Negeri (MAN) 2 Pontianak in learning mathematics using e-learning of madrasah. The research method used is a qualitative descriptive research method in the form of ex-post facto research. The subjects in this study were students in class XI, which consisted of 36 students in class XI MIPA 1, class XI MIPA 2 with 34 students, class XI MIPA 3 with 35 students in class XI MIPA 4 with 35 students and all 6 mathematics teachers. The instruments used in this study were questionnaires and interviews. Based on the results of the study, it was found that the implementation of mathematics learning using e-learning madrasah consisted of preliminary activities, core activities, and closing activities. Many students experience problems influenced by internal and external factors in learning mathematics using e-learning madrasah.